Managing post-harvest diseases in onion - Salunkhe, Vanita; Gawande, S J; Singh, Major (Indian Horticulture, 2019)
Nearly 15 fungal and 5 bacterial species are responsible for majority of thepost-harvest diseases in storage and transit all over the world. The commonconsequence of post harvest diseases is bulb rotting, poor marketable qualityand shorter shelf-life. The destructive diseases in storage are black mould(Aspergillus niger), blue mould (Penicillium spp.), onion smudge(Colletotrichum circinans), botrytis rot (Botrytis spp.) and bacterial rots. Goodagriculture practices and proper post-harvest management play a key rolein reducing the storage losses due to diseases. Therefore, major post-harvestdiseases in onion and their management practices are explained.